Effect of Service Quality and Customer Relationship Management on Customer Loyalty: Company Image as an Intervening Variable - Sholihah, Ainun Kholbi; Winarto, Winarto -; Farouk, Umar - (JOBS (Jurnal Of Business Studies), 2023)
This research aims to analyze the influence of service quality and customer relationship management through the company's image on the customer loyalty of Alfamart in Semarang City. The sampling method uses a purposive sampling technique, number of 100 respondents. The data collection methods used are questionnaires, and interviews. The analysis method is path analysis with 2 structural models. The results of the reseach found that there was a significant influence between service quality and customer relationship management at Alfamart customer loyalty in Semarang City. There is a significant positive influence between service quality, customer relationship management, and company image on customer loyalty. Meanwhile, in the multiple linear regression analysis, it found that service quality has a direct effect on customer loyalty; customer relationship management also has a direct effect on customer loyalty. In this research, it was also found that the quality of service has an indirect influence on customer loyalty through the company's image. Customer relationship management also has an indirect influence on customer loyalty through the company's image